Community Action Targeting Children who Are Homeless (CATCH): Addressing the Mental Health and Developmental Needs of Children Experiencing Homelessness. Issue 3 (July 2014) - Donlon, Peter; Lake, Jason; Pope, Emma; Shaw, Christine; Haskett, Mary E.
The purpose of this article is to describe a collaborative community project designed to enhance the mental health and development of children experiencing family homelessness. In spite of the many risk factors faced by children without homes, there has been limited attention to understanding and addressing their needs. Community Action Targeting Children who are Homeless (CATCH) was developed by a group of community leaders in family homelessness and experts in young children's mental health; the goal of CATCH is to promote the social–emotional adjustment and developmental status of children who are homeless. In this article we provide a rationale for the project, discuss the goals and strategies implemented to meet those goals, and describe the lessons learned.